Mosque-Based Community Empowerment in Improving the Quality of Reading and Writing the Qur'an at Al-Insaf Mosque, Glinggangan Village - Ridho Riyanto Riyanto (Institut Studi Islam Muhammadiyah Pacitan, 2025)
Mosques have a strategic role not only as a place of ritual worship, but also as a center for education and community empowerment. However, in rural communities, there is still a problem of low quality of reading and writing of the Qur'an (BTQ), especially in adolescent and adult groups. This community service program aims to improve the quality of community BTQ through an empowerment approach based on the Al-Insaf Mosque in Glinggangan Village. The method used is Community Development with a Participatory Action Research (PAR) approach, which actively involves the community from the stage of identifying needs, planning, implementing, and evaluating programs. Service activities include the formation of routine BTQ classes, assistance in reading and writing the Qur'an, learning basic tajweed, and practicing writing hijaiyah letters and verses of the Qur'an. The results of the service showed an increase in the ability to read the Qur'an according to the rules of tajweed, an increase in hijaiyah writing skills, and a growth in community interest and participation in mosque-based religious activities. In addition, this program has succeeded in forming sustainable BTQ classes and local cadres of BTQ teachers as the internal drivers of the mosque. These findings show that a mosque-based participatory approach is effective in improving people's Qur'an literacy and strengthening the role of mosques as a center for literacy and religious empowerment of rural communities.